Devices and techniques for bariatric and metabolic endoscopy: European Society of Gastrointestinal Endoscopy (ESGE) Technical and Technology Review : technical review - Boškoski, Ivo; Matteo, Maria Valeria; Shamah, Steven; Dayyeh, Barham K. Abu; Bove, Vincenzo; Siena, Martina De; Huberty, Vincent; Maselli, Roberta; Perretta, Silvana; Pontecorvi, Valerio; Stier, Christine; Sharaiha, Reem Z.; et al. (Endoscopy, 2025)
Endoscopic bariatric and metabolic therapies (EBMTs) are increasingly recognized as valuable tools for managing obesity and related metabolic disorders. As the prevalence of obesity continues to rise globally, there is a growing demand for effective, safe, and less invasive treatment options. This review provides a comprehensive summary of the available EBMTs, including both stomach-targeted and small-bowel-targeted devices. The review details the various devices, outlines the techniques for their proper use, and discusses their indications. It also presents data on their efficacy and safety, and the management of adverse events and weight regain, as well as anticipated future developments. The paper emphasizes the necessity for additional high quality randomized controlled trials and long-term outcome data to better define the role of these therapies within obesity treatment protocols. Overall, this review serves as an authoritative resource for endoscopists, bariatric specialists, and the wider healthcare community involved in obesity care, promoting best practices and guiding the appropriate implementation of EBMTs in clinical settings.